2018
DOI: 10.17085/apm.2018.13.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Modern techniques to optimize neuraxial labor analgesia

Abstract: Neuraxial analgesia is the gold standard method for pain relief in labor. Several techniques can optimize both the initiation and maintenance of neuraxial labor analgesia. Initiation techniques such as combined spinal-epidural or dural puncture epidural may offer some advantages over standard epidural insertion. The use of ultrasound to assist with landmarking and optimizing block placement improves neuraxial success, and is particularly useful in certain patient populations. Maintaining labor analgesia with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…Besides, CSE provides better quality analgesia throughout labor. [ 16 ] Our results are in line with previous studies,[ 13 17 18 ] which found no difference in physician top-up boluses between CSE and EPL techniques. In contrast, one study[ 19 ] showed more physician top-up boluses with CSE (36%) versus epidural (27%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, CSE provides better quality analgesia throughout labor. [ 16 ] Our results are in line with previous studies,[ 13 17 18 ] which found no difference in physician top-up boluses between CSE and EPL techniques. In contrast, one study[ 19 ] showed more physician top-up boluses with CSE (36%) versus epidural (27%).…”
Section: Discussionsupporting
confidence: 92%
“…Another objection to the use of CSE is an increased incidence of hypotension, fetal bradycardia, nausea, and vomiting. [ 16 22 ] However, our results agree with previous studies[ 14 22 ] which failed to find a significant difference between CSE and EPL.…”
Section: Discussionsupporting
confidence: 92%
“…The medication and techniques for labor analgesia in obese parturients are not significantly different from those in mothers of normal weight. Patient-controlled epidural analgesia (PCEA) and programmed intermediate epidural boluses are widely used and dilute low concentrations of local anesthetics ( < 0.1% bupivacine or equivalent potency of ropivacaine) mixed with opioids (fentanyl or sufentanil) are recommended as medications [30].…”
Section: Analgesia For Labormentioning
confidence: 99%